Opportunity Cost of Surgical Management of Craniomaxillofacial Trauma. Issue 1 (March 2016) - Moses, Helen; Powers, David; Keeler, Jarrod; Erdmann, Detlev; Marcus, Jeff; Puscas, Liana; Woodard, Charles
The provision of trauma care is a financial burden, continually associated with low reimbursement, and shifts the economic burden to major trauma centers and providers. Meanwhile, the volume of craniomaxillofacial (CMF) trauma and the number of surgically managed facial fractures are unchanged. Past financial analyses of cost and reimbursement for facial trauma are limited to mandibular and midface injuries, consistently revealing low reimbursement. The incurred financial burden also coincides with the changing landscape of health insurance. The goal of this study is to determine the opportunity cost of operative management of facial trauma at our institution. From our CMF database of greater than 3, 000 facial fractures, the physician charges, collections, and relative value units (RVUs) for CMF trauma per year from 2007 to 2013 were compared with a general plastic surgery and otolaryngology population undergoing operative management during this same period. Collection rates were analyzed to assess if a significant difference exists between reimbursement for CMF and non-CMF cases. Results revealed a significant difference between the professional collection rate for operative CMF trauma and that for other operative procedures (17.25 vs. 29.61%, respectively; p < 0.0001). The average number of RVUs billed per provider for CMF trauma declines significantly, from greater than 700 RVUs to 300 over the study period, despite a stable volume. Surgical management of CMF trauma generates an unfavorable financial environment. The large opportunity cost associated with offering this service is a potential threat to the sustainability of providing care for this population.